Improving financial management efficiency at BAHANA Ciawi Clean Water Facility via an Android-based mobile application - Dwi Andini Putri; Siti Ernawati; Hasanudin Hasanudin (University of Merdeka Malang, 2024)
KSM SAB BAHANA in Ciawi, Bogor is a Community Self-Help Group (KSM) for Clean Water Facilities (SAB) BAHANA located in Kampung Tipar RT 01, RW 04 Ciawi. KSM SAB BAHANA was formed based on Decree Number 36 on December 31, 2019. Currently, there are significant problems in managing clean water services, especially in terms of customer registration and management of financial reports which are still done manually. This condition causes inefficiency and has the potential to cause recording errors. To overcome these challenges, community service is carried out by introducing an Android-based application designed to improve the efficiency and accuracy of financial management. The purpose of this service is to provide a technological solution that facilitates customer registration and management of financial reports effectively. The methods used include data collection, application design, socialization, implementation, evaluation, and ongoing maintenance to ensure the successful implementation of the application. The evaluation results show that 86 percent of the community strongly agree with the use of this application, which confirms that this program has succeeded in helping residents and SAB BAHANA officers manage customer reports and data better and more sustainably.